Film adaptation as the interface between creative translation and cultural transformation: The case of Baz Luhrmann's The Great Gatsby - Katerina Perdikaki (JoSTrans: The Journal of Specialised Translation)
Adaptation is prominent in many facets of the creative industries, such as the performing arts (e.g. theatre, opera) and various forms of media (e.g. film, television, radio, video games). As such, adaptation can be regarded as the creative translation of a narrative from one medium or mode to another. This paper focuses on film adaptation and examines its role in cultural production and dissemination within the broader polysystem (Even-Zohar 1978a). Adaptation has been viewed as a process which can shed light on meaningful questions on a social, cultural and ideological level (cf. Casetti 2004; Corrigan 2014; Venuti 2007). Nevertheless, an integrated framework for the systematic analysis of adaptations seems to have remained under-researched. The paper puts forward a model for adaptation analysis which highlights the factors that condition adaptation as a process and as a product. In this way, adaptation is studied as a system monitored by economic, creative and social agendas which nevertheless transforms the communicating vessels of the literary system and the film industry. To illustrate this, the paper discusses how the two systems and various creative and socioeconomic considerations interlace in the latest film adaptation of The Great Gatsby (Luhrmann 2013). It concludes on the benefits of a holistic approach to adaptation.